2006
DOI: 10.1124/dmd.106.012765
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MRP1/ABCC1, MRP2/ABCC2, and MRP3/ABCC3 by Nucleoside, Nucleotide, and Non-Nucleoside Reverse Transcriptase Inhibitors

Abstract: ABSTRACT:Many drug interactions with drugs used for the therapy of human immunodeficiency virus (HIV) occur at the level of different cytochrome P450 isozymes. Increasing evidence suggests that antiretrovirals may also modify activity and expression of active drug transport systems. Such interactions may alter drug absorption, elimination, and also drug distribution and reach clinical importance if thereby access to the target site is affected. Beyond P-glycoprotein, the family of multidrug resistance-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 30 publications
3
81
1
Order By: Relevance
“…Efavirenz reduces, for example, the in vivo concentrations of the MRP2 substrate pravastatin by 40%, which cannot be attributed to CYP-induction because this drug is hardly metabolized via this system (36). Earlier studes have demonstrated that efavirenz can also significantly inhibit at least the ABC-transporters P-gp /ABCB1, BCRP /ABCG2, and MRP1-3 / ABCC1-3 at concentrations ≥10 μM (24,37,38), implying that inducing effects might be superimposed in vivo by inhibiting effects of this compound. Which effect preponderates in vivo can only be clarified in appropriate clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Efavirenz reduces, for example, the in vivo concentrations of the MRP2 substrate pravastatin by 40%, which cannot be attributed to CYP-induction because this drug is hardly metabolized via this system (36). Earlier studes have demonstrated that efavirenz can also significantly inhibit at least the ABC-transporters P-gp /ABCB1, BCRP /ABCG2, and MRP1-3 / ABCC1-3 at concentrations ≥10 μM (24,37,38), implying that inducing effects might be superimposed in vivo by inhibiting effects of this compound. Which effect preponderates in vivo can only be clarified in appropriate clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluation of possible MRP1 inhibiting properties of the oxaliplatin metabolites oxalate and DACH, both compounds were studied in a MRP1 inhibition assay as described elsewhere [26] with minor modifications. In brief, MDCKII cells over-expressing MRP1 ( …”
Section: Impact Of Oxaliplatin Metabolites On Mrp1 Activitymentioning
confidence: 99%
“…The uptake studies were carried out as described previously (El Hafny et al, 1997) with minor modifications. Briefly, BT4C cells grown onto 24-well plates were washed twice with uptake buffer [129 mM NaCl, 0.63 mM CaCl 2 , 2.5 mM KCl, 0.74 mM MgSO 4 , 7.4 mM Na 2 HPO 4 , 1.3 mM KH 2 PO 4 , 5.3 mM D-glucose, and 10 mM Hepes (pH 7.4)] and then preincubated with or without the P-glycoprotein inhibitor GF120918 (Wallstab et al, 1999) (3 mM), the inhibitor of multidrug resistance-associated protein (MRP) family transporters MK-571 (Weiss et al, 2007) H]CPT were used as positive reference compounds to assess the functionality of P-glycoprotein and MRP family transporters, as these compounds have been shown to be ABC transporter substrates (Kemper et al, 2003;Tian et al, 2005). After the preincubation, [ 3 H]GCV (0.5 mCi/ml, 0.12 mM) and the reference compounds [ 3 H]TAX (0.5 mCi/ml, 9.2 nM) and [ 3 H]CPT (0.5 mCi/ml, 33 nM) prepared either in the fresh uptake buffer or in the uptake buffer including GF120918 (3 mM), MK-571 (50 mM), or GCV (100 mM) were added to the cells and incubated at 37°C on a stirring platform for 120 minutes.…”
Section: Methodsmentioning
confidence: 99%